Ethanol Extract of Magnolia officinalis Prevents Lipopolysaccharide‐Induced Memory Deficiency via Its Antineuroinflammatory and Antiamyloidogenic Effects. (25th May 2012) - Lee, Young‐Jung; Choi, Dong‐Young; Yun, Yeo‐Pyo; Han, Sang Bae; Kim, Hwan Mook; Lee, Kiho; Choi, Seok Hwa; Yang, Mhan‐Pyo; Jeon, Hyun Soo; Jeong, Jea‐Hwang; Oh, Ki‐Wan; Hong, Jin Tae
Abstract : Magnolia bark contains several compounds such as magnolol, honokiol, 4‐ O ‐methylhonokiol, obovatol, and other neolignan compounds. These compounds have been reported to have various beneficial effects in various diseases. There is sufficient possibility that ethanol extract of Magnolia officinalis is more effective in amyloidogenesis via synergism of these ingredients. Neuroinflammation has been known to play a critical role in the pathogenesis of Alzheimer's disease (AD). We investigated whether the ethanol extract of M. officinalis (10 mg/ kg in 0.05% ethanol) prevents memory dysfunction and amyloidogenesis in AD mouse model by intraperitoneal lipopolysaccharide (LPS, 250 µg/ kg/day for seven times) injection. We found that ethanol extract of M. officinalis prevented LPS‐induced memory deficiency as well as inhibited the LPS‐induced elevation of inflammatory proteins, such as inducible nitric oxide synthase and cyclooxygenase 2, and activation of astrocytes and microglia. In particular, administration of M. officinalis ethanol extract inhibited LPS‐induced amyloidogenesis, which resulted in the inhibition of amyloid precursor protein, beta‐site amyloid‐precursor‐protein‐cleaving enzyme 1 and C99. Thus, this study shows that ethanol extract of M. officinalis prevents LPS‐induced memory impairment as well as amyloidogenesis via inhibition of neuroinflammation and suggests that ethanol extract of M. officinalis might be a useful intervention for neuroinflammation‐associated diseases such as AD. Copyright © 2012 John Wiley & Sons, Ltd.